Drivers of vegetable consumption in urban Nigeria: Food choice motives, knowledge, and self-efficacy - Raaijmakers, Ireen; Snoek, Harriette, Snoek; Maziya-Dixon, Busie; Achterbosch, Thom (MDPI, 2018)
Objective: This study aimed to provide insights into vegetable consumption behavior of urban Nigerian consumers across different Socio-Economic Classes (SEC), their main food choice motives, and the associations of these motives and other drivers with vegetable consumption. Methods: An online survey was conducted in which 1220 women from Lagos (N = 808) and Ibadan (N = 412) metropolis from different SEC participated. Results: On average, respondents reported to consume 2.6 portions of vegetables per day. Most vegetables were bought at open and traditional markets, were bought fresh rather than processed, and were consumed cooked. Respondents from the second richest and upper middle SEC consumed most vegetables () and higher SEC consumed a larger variety of vegetables compared to those from lower classes. Respondents who reported to have a higher knowledge of vegetable consumption, had a higher belief in one’s own ability to prepare vegetables (self-efficacy), and those that valued the food motive Mood and Health more, reported a higher vegetable intake. Conclusions: Vegetable consumption in the studied cities in Nigeria was below recommendations. Increasing knowledge and self-efficacy might be a way to increase consumption, especially in combination with interventions in the food environment and product design focused on the motives Health and Mood, and considering the importance of differences between SEC.